ANALISIS PENGENDALIAN PENULARAN SKABIES DI PONDOK PESANTREN DARUSSALAM KABUPATEN BANYUWANGI - Wa Rina (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2017)
Islamic boarding schools are a public place and can be a disease transmission facility, if hygiene and sanitation are not properly maintained. One of the infections that occur in Islamic boarding schools is scabies. The purpose of this study is how to analyze scabies in Darussalam Islamic boarding schools. Independent variables are management of Islamic boarding schools, students of personal hygiene, and boarding schools for environmental sanitation. Analytical research with cross sectional design. The sample size is 109 students with simple random sampling. Logistic regression test results obtained temperature (p-value = 0.075, OR = 0.901) and humidity (p-value = 0.047, OR = 0.885). Conclusions are the factors that most influence the incidence of scabies in Islamic boarding schools are temperature and humidity. There are more efforts for promotive and preventive activities from boarding schools and students must be approved by the head of the lodge and the head of the lodge. Students cannot use toiletries, clothes, towels and also must open the window, not open their clothes, do not stack the cardboard in the room so that the temperature and humidity remain good.